2020
DOI: 10.1111/febs.15241
|View full text |Cite
|
Sign up to set email alerts
|

Lack of orientation selectivity of the heme insertion in murine neuroglobin revealed by resonance Raman spectroscopy

Abstract: Different murine neuroglobin variants showing structural and dynamic alterations that are associated with perturbation of ligand binding have been studied: the CD loop mutants characterized by an enhanced flexibility (Gly‐loop40–48 and Gly‐loop44–47), the F106A mutant, and the double Gly‐loop44–47/F106A mutant. Their ferric resonance Raman spectra in solution and in crystals are almost identical. In the high‐frequency region, the identification of a double set of core size marker bands indicates the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 47 publications
(268 reference statements)
4
33
0
Order By: Relevance
“…The vinyl stretching modes [ν(C=C), in blue] at 1,620 and 1,630 cm −1 (Figures 4C,D) are identical for all the spectra. The frequencies are sensitive to their orientations with respect to the porphyrin plane (Marzocchi and Smulevich, 2003), indicating trans and cis configurations, respectively (Milazzo et al, 2020). , and their mutants.…”
Section: Heme Environment In Wild-type and Mutated Globinsmentioning
confidence: 99%
“…The vinyl stretching modes [ν(C=C), in blue] at 1,620 and 1,630 cm −1 (Figures 4C,D) are identical for all the spectra. The frequencies are sensitive to their orientations with respect to the porphyrin plane (Marzocchi and Smulevich, 2003), indicating trans and cis configurations, respectively (Milazzo et al, 2020). , and their mutants.…”
Section: Heme Environment In Wild-type and Mutated Globinsmentioning
confidence: 99%
“…Comparison of the experimental conditions is reported in Table 3. From Milazzo et al [43] [Colour figure can be viewed at wileyonlinelibrary.com] Note: From Milazzo et al [43] protein displaying both the canonical and reversed heme orientations. Interestingly, The X-ray data showed that the two conformers are structurally different.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the combination of RR spectroscopy on single crystal and solution samples has proved to be a sensitive diagnostic tool that could be extended to other heme proteins to detect heme F I G U R E 1 0 Low wavenumber region resonance Raman (RR) spectra of ferric murine Ngb WT (bottom) and the Gly-loop [44][45][46][47] /F106A mutant (top), in solution, taken with a 413.1 nm excitation. Adapted from Milazzo et al [43] [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The band at around 1,614 cm −1 contains contributions from the two vinyl side chains of hemin that converge at the same wavenumber value due to the coplanar orientation of both groups with the porphyrin plane (Milazzo et al, 2020). On SERS substrates (see Figure 6A), the wavenumber value of the 1,614 cm −1 band undergoes a gradual down-shift when glyphosate concentration is increased in the hemin solution, reaching a value of 1,609 cm −1 at the highest tested concentration (1×10 −5 M).…”
Section: Origin Of the Sers Effectmentioning
confidence: 99%